1973
DOI: 10.1530/jrf.0.0350321
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Electrophoretic Characteristics of Bovine Rete Testis Fluid and Plasma From the Cauda Epididymidis

Abstract: Polyacrylamide gel electrophoresis was used to evaluate rete testis fluid (RTF) and plasma from the cauda epididymidis (CEP) obtained from conscious Holstein bulls. The major protein in RTF had an electrophoretic mobility similar to that of blood serum albumin, but the seemingly analogous protein in CEP had a slower relative mobility. Bovine CEP contains at least three proteins, one glycoprotein and possibly three other PAS-positive components not detected in RTF or blood serum. In addition, esterases, acid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…The seminiferous tubular fluid (d) contained a number of protein bands which were absent from blood serum. This confirms previous results that the testis secretes specific proteins into the lumen (Amann et al 1973;Koskimies & Kormano 1973;Turner et al 1979). The observation that many of the testicular protein bands were reduced in concentration or absent from the fluid of the caput epididymidis suggests that some of the testicular proteins were reabsorbed by efferent ducts or the initial segment.…”
Section: Biochemical Analysis Of Secretionsupporting
confidence: 92%
“…The seminiferous tubular fluid (d) contained a number of protein bands which were absent from blood serum. This confirms previous results that the testis secretes specific proteins into the lumen (Amann et al 1973;Koskimies & Kormano 1973;Turner et al 1979). The observation that many of the testicular protein bands were reduced in concentration or absent from the fluid of the caput epididymidis suggests that some of the testicular proteins were reabsorbed by efferent ducts or the initial segment.…”
Section: Biochemical Analysis Of Secretionsupporting
confidence: 92%
“…Over the years, several investigators have observed that many of the proteins present in epididymal luminal fluid, in a variety of species, differ from those present in serum and rete testis fluid (Alumot et al, 1971;Amann et al, 1973;Jones, 1987;Olson and Hinton, 1985;Turner et al, 1979). Moreover, the combination of various techniques of micropuncture with gel electrophoresis made it possible to determine that the luminal composition of epididymis-specific proteins varies along the length of the epididymis (Olson and Hinton, 1985;Turner et al, 1979;Wong et al, 1981).…”
Section: Macromolecular Luminal Fluid Microenvironmentmentioning
confidence: 99%
“…The fate and significance of most of these proteins is unknown. Recently, it has been shown electrophoretically that bovine epididymal plasma from the cauda region contains at least three proteins not detected in the rete testis fluid or serum (Amann, Killian & Benton, 1973).…”
Section: Reabsorbedmentioning
confidence: 99%